Numerical simulation of coarsening in binary solder alloys - Gräser, Carsten; Kornhuber, Ralf; Sack, Uli (Computational Materials Science, 2014)
Coarsening in solder alloys is a widely accepted indicator for possible failure of joints in electronic devices. Based on the well-established Cahn-Larché model with logarithmic chemical energy density (Dreyer and Müller, 2001) [20], we present a computational framework for the efficient and reliable simulation of coarsening in binary alloys. Main features are adaptive mesh refinement based on hierarchical error estimates, fast and reliable algebraic solution by multigrid and Schur-Newton multigrid methods, and the quantification of the coarsening speed by the temporal growth of mean phase radii. We provide a detailed description and a numerical assessment of the algorithm and its different components, together with a practical application to a eutectic AgCu brazing alloy. © 2014 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2022-03-23
Keywords: Adaptive finite elements; Cahn-Larché system; Phase separation; Schur-Newton multigrid